Exploring price and non-price determinants of trade flows in the largest euro-area countries - Claire Giordano; Francesco Zollino (European Central Bank (ECB), 2015)
Since the mid-2000s price-competitiveness indicators for some euro-area countries have been providing conflicting signals. Against a stability of the producer price (PPI)-based measure, the manufacturing unit labour cost (ULCM)-deflated indicator points to a major competitiveness loss in Italy; we argue that the discrepancy mostly reflects a divergence of ULCM and PPI trends in competitor countries. Owing to the fading representativeness of labour on overall costs, price-based indicators appear to be more appropriate than those based on ULCMs to assess external competitiveness. In Italy ULC-based indicators play a less relevant role relative to price-deflated measures in explaining exports; the opposite holds true for Germany and France, whereas in Spain exports are insensitive to prices. Non-price competitiveness proves important in explaining Italian, German and, in particular, Spanish exports. Imports react to price-competitiveness dynamics only in Italy; considering the participation in global value chains is useful to correctly identify import sensitivity to domestic and foreign demand.
Keywords: F14; F62; 330; non-price competitiveness; price competitiveness; producer prices; unit labour costs